Pendampingan Perencanaan Mix Mode Hemat Energi pada Rumah Baca Supiturang, Kecamatan Karangploso, Kabupaten Malang - Cynthia Permata Dewi; Apif Miptahul Hajji; Imam Alfianto (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2021)
Lighting strategy in a building play important role, especially for building with specific function like a small community library in Supiturang. An appropriate lighting design will help user inside the building doing their activities comfortably. The daylight as the primary source of lighting in a building which also can save electricity energy should utilized well. This paper promotes the use of mix model lighting strategies between natural and artificial lighting in order to reach visual comfort inside the building. Department of Civil Engineering, Faculty of Engineering, State University of Malang take place as an academics to share knowledge in the society in Supiturang village. The mixed used design of natural and artificial design strategy was used to save electricity energy in building and optimize the visual comfort for reading activities. Methods that used in this community service activity were interview, field survey to get building physical data and simulation of lighting design. During the covid-19 situation, in the beginning there was a problem in executing this activity. Since the policy on the village was not allowing to gather many people in the small community library, of Supiturang village, thus the proposed design was only explained to the head of the Supiturang village as the policy holders. DOI: https://doi.org/10.26905/abdimas.v6i1.4995